Research on the measurement and spatiotemporal evolution characteristics of new quality productive forces in China’s marine economy - Xue Jin; Xue Jin; Yanwei Wang; Yanwei Wang; Kedong Yin; Kedong Yin (Frontiers in Marine Science)
The marine economy’s new quality productive forces is an important driving force to promote the high-quality development of the marine economy. Exploring the level of marine economy’s new quality productive forces and its spatiotemporal evolution law will help to provide solid theoretical support and empirical basis for formulating scientific strategies to promote the accelerated development of marine economy. Based on panel data from 11 coastal provinces and cities from 2010 to 2022, this study applies the entropy value method to measure the level of marine economy’s new quality productive forces, and then uses the Dagum Gini coefficient and its decomposition, kernel density estimation method and spatial Markov chain model to reveal its regional differences and spatiotemporal evolution characteristics. The results of the study showed that: (1) The level of marine economy’s new quality productive forces in China and the three major marine economic circles (northern, eastern and southern) have grown annually, but regional imbalances are increasing. Among the constituent elements, scientific and technological productive forces exhibited the strongest growth momentum, while the development of green productive forces relatively lagged behind. (2) The level of marine economy’s new quality productive forces in individual provinces deviates significantly from the national average, resulting in supervariable density becoming the main source of spatial differentiation of marine economy’s new quality productive forces level. (3) Except for the eastern marine economic circle, other regions generally show obvious polarization, which not only limits the effective allocation of resources, but also affects the rational flow and transfer of new quality productive forces levels between different regions. In this regard, relevant policy recommendations are put forward: (1) The implementation of differentiated strategies promotes the regional adaptive development of marine economy’s new quality productive forces. (2) Strengthening internal and external linkage mechanisms to release the spillover effect of the marine economy’s new quality productive forces. (3) Science and technology drive green development and enhance the green content of marine economy’s new quality productive forces.